Opposing roles of Fos, Raw, and SARM1 in the regulation of axonal degeneration and synaptic structure - Waller, Thomas J.; Collins, Catherine A. (Frontiers in Cellular Neuroscience, 2023)
The degeneration of injured axons is driven by conserved molecules, including the sterile armadillo TIR domain containing protein SARM1, the cJun N-terminal kinase JNK, and regulators of these proteins. These molecules are also implicated in the regulation of synapse development, though the mechanistic relationship of their functions in degeneration versus development are poorly understood. Here we uncover disparate functional relationships between SARM1 and the transmembrane protein Raw in the regulation of Wallerian degeneration and synaptic growth in Drosophila motoneurons. Our genetic data suggest that Raw antagonizes the downstream output MAP Kinase signaling mediated by Drosophila SARM1 (dSarm). This relationship is revealed by dramatic synaptic overgrowth phenotypes at the larval neuromuscular junction when motoneurons are depleted for Raw or overexpress dSarm. While Raw antagonizes the downstream output of dSarm to regulate synaptic growth, it shows an opposite functional relationship with dSarm for axonal degeneration. Loss of Raw leads to decreased levels of dSarm in axons and delayed axonal degeneration that is rescued by overexpression of dSarm, supporting a model that Raw promotes the activation of dSarm in axons. However, inhibiting Fos also decreases dSarm levels in axons, but has the opposite outcome of enabling Wallerian degeneration. The combined genetic data suggest that Raw, dSarm and Fos influence each other's functions through multiple points of regulation to control the structure of synaptic terminals and the resilience of axons to degeneration.